Efeito in vitro de nanopartículas de quitosana na biocorrosão do esmalte dentário - França, Renata Cristina Sobreira (2016)
Chitosan is a biopolymer that has an antimicrobial activity against oral pathogens, but its effect on the prevention of enamel demineralization enslaving an erosive challenge has been little investigated. The objective of the study was to evaluate the effect of dispersed chitosan nanoparticles (ChNP) in solution in the prevention of the demineralization of dental enamel submitted to erosive challenge. A solution of ChNP at the concentration of 3.85 mg / mL was obtained by ionic gelation. (4 x 4 mm) and 4 groups were formed (n = 26) according to the tested solutions: G1 - 3.85 mg / mL ChNP; G2 - 0.5 mg / mL sodium fluoride (NaF) solution (positive control); Solution of G3-chitosan 5 mg / mL; G4 - distilled water (negative control). As the samples were made in 1% citric acid monohydrate to 90, washed in distilled water and then for 2 hours in remineralizing solution and washed with distilled water. This cycle was repeated 4 times daily for 7 days. After a 1st and 4th exposure to acid, how its solutions will be applied in each group, for 2 minutes and in terms of remineralizing solution. At the end of each day, like samples in remineralizer. The Vickers hardness (VHN) (n = 26), and an analysis of tooth wear by profilometry (n = 15) were before and after the erosive challenge. The percentage of hardness loss (% SMH) was performed after the challenge. Data were analyzed by Anova and Tukey with a = 0.05. There was a statistically significant difference in the values of VHN and% of SMH only with the negative control group, which presented lower hardness (258.3 ± 41.9) and higher% SMH (34.5 ± 10.5). Among the test solutions there is no statistical difference. (4.4 ± 0.3 µm) Chitosan (4.5 ± 0.4 µm) ChNP (3.0 ± 0.4 µm) 0.4 µm NaF (1.2 ± 0.3 µm). Conclusion: As the chitosan nanoparticles decreased enamel wear caused by dental erosion.